Smart Home Menggunakan PLC Outseal Berbasis Internet Of Things - NANDO, ARDI MARTIA; FITRIANI, ENDAH (Jurnal Ampere, 2023)
Smart Home is actually a technology-based home. Smart Home technology is increasingly being developed after the discovery of Internet Of Things (IoT) Technology, where home appliances such as lights, fans, televisions, and fences can be controlled remotely. The purpose of this research is to develop a smart home technology that has been made before, by using the Outseal PLC as a controller, the ESP 8266 module as a liaison to the Blynk application, then using a photocell sensor, and a PIR sensor. The way this tool works is when the photocell sensor detects a room that lacks light, the lights will turn on automatically, and turn off automatically when the room gets enough light, and the function of the PIR sensor is to turn on the fan automatically when it detects movement of people entering the room. However the lights and fans can be controlled manually and controlled remotely using the Blynk App. From the results of the tests that have been carried out, the blynk application designed to control the opening and closing of the gate can work well. The PIR sensor works up to a distance of 20 meters, while the lack of light in the room can be detected by the photocell sensor